EKSKLUSI PEREMPUAN, SASTRA, DAN PSIKOLOGI GENDER: STUDI PADA CERPEN KARYA BUDI DARMA TAHUN 2016—2020 [Female Exclusion, Literature, and Gender Psychology: Study On Budi Darma's Short Stories 2016—2020] - Anas Ahmadi (TOTOBUANG, 2021)
The study of gender is currently attracting the researchers from various fields. One of them is  research gender in literature. Therefore, this study aims to describe the exclusion of women contained in Indonesian literature through a gender psychology perspective. The method used qualitative with narrative exposure style. The data source used a short story by Budi Darma in 2016-2020. Data analysis techniques includes identification, classification, and data exposure. The results of the study and discussion showed that exclusion in literature emerged some categories: (1) exclusion of women through the selection of short story titles that were more tendent to men, (2) exclusion of wartime women, and (3) exclusion of women through labeling. Studi mengenai gender saat ini menarik perhatian peneliti berbagai bidang. Salah satunya adalah penelitian gender di bidang sastra. Berkait dengan itu, penelitian ini bertujuan untuk mendeskripsikan eksklusi perempuan yang terdapat dalam sastra Indonesia melalui perspektif psikologi gender. Metode yang digunakan adalah kualitatif dengan gaya pemaparan naratif. Sumber data yang digunakan adalah cerpen karya Budi Darma tahun 2016-2020. Teknik analisis data meliputi, identifikasi, klasifikasi, dan pemaparan data. Hasil penelitian dan pembahasan menunjukkan bahwa eksklusi dalam literatur muncul dengan kategori (1) eksklusi perempuan melalui pemilihan judul cerpen yang lebih condong kepada laki-laki, (2) eksklusi perempuan masa perang, dan (3) eksklusi perempuan. melalui pelabelan.